Midwives' Evaluation of a Neonatal Resuscitation in High- and Low-Resource Settings - Francesco Cavallin; Serena Calgaro; Serena Calgaro; Martina Borellini; Martina Borellini; Margherita Magnani; Margherita Magnani; Greta Beltramini; Amir Hussein Abubacar Seni; Bonifacio Rodriguez Cebola; Ana Nicolau Tambo; Giovanni Putoto; et al. (Frontiers Media S.A., 2021)
Aim: To assess midwives' evaluation of a real-life neonatal resuscitation and their opinion on importance of resuscitation interventions.Methods: Multicenter, multi-country study.Setting: Beira Central Hospital (Mozambique) and Azienda Ospedale-Università di Padova (Italy).Subjects: Sixteen Mozambican midwives and 18 Italian midwives.Interventions: Midwives' assessment was evaluated by using a predefined score, which graded each resuscitation intervention (0-2 points) and summed to a total score for each step (initial steps, bag-mask ventilation, and chest compressions). All scores were compared with referral scores given by two expert neonatologists.Results: Both Mozambican and Italian midwives overestimated their performance regarding of initial steps taken during resuscitation, chest compressions, high-oxygen concentrations (p < 0.01), and underestimated the importance of stimulation (p < 0.05). Mozambicans overestimated suctioning (p < 0.001). Participants agreed with experts about the importance of equipment preparation, using a warmer, drying the newborn, removing wet linen and heart rate assessment.Conclusion: Mozambican and Italian midwives overestimated the performance of a real-life neonatal resuscitation, with heterogeneous evaluation of the importance of several aspects of neonatal resuscitation. These findings may be useful for identifying educational goals.